Agents in Principle, Agents in Practice 14th International Conference, PRIMA 2011, Wollongong, Australia, November 16-18, 2011. Proceedings - Kinny, David; aHsu, Jane Yung-jen; aGovernatori, Guido; aGhose, Aditya K. (Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the 14th International Conference on Principles and Practice in Multi-Agent Systems, PRIMA 2011, held in Wollongong, Australia, in November 2011. The 39 papers presented together with 3 invited talks were carefully reviewed and selected from numerous submissions. They focus on practical aspects of multiagent systems and are organised in topical sections on coalitions and teamwork, learning, mechanisms and voting, modeling and simulation, negotiation and coalitions, optimization, sustainability, agent societies and frameworks, argumentation, and applications.